HOW CAN MICROSOFT WORD PROGRAM HELPS TO REDUCE LANGUAGE INEQUALITIES CREATED BY REFUGEES IN THE NEW GREEK SCHOOLS - Drougas, Vasileios Ag. (Uniqbu Journal of Social Sciences, 2021)
The refugee problem in Greece has raised important language issues. The Greek language is difficult to spell, it creates additional difficulties for refugees who come mainly from the regions of Asia. The present study presents a presentation of the use of the Microsoft Word program that is very common today in basic computer programs. The use of the basic word program is presented to help the refugees to write the Greek language correctly. Thus this simple tool can accomplish the basic education of writing and reading the Greek language helping refugees to integrate more easily into the Greek educational and social community. Using a simple study of the spelling and speech offered by the Microsoft program, every refugee can learn the Greek language much more easily and pronounce the words and spell correctly. In this study, basic and characteristic examples are presented that can help the teacher to create important lessons for the integration of refugees in Greek educational programs.